Cratonic basin formation : a case study of the Parnaíba Basin of Brazil - Daly, Michael C. (Geologist); Fuck, Reinhardt A.; Julia, Jordi (Geologist); Macdonald, David; Watts, A. B. 1945- (The Geological Society, 2018)
Cratonic basins are large, distinctive features of the continental crust. They are preferentially developed on thick continental lithosphere, are typically sub-circular in shape and subside over periods of hundreds of millions of years. They are also endowed with significant resources. However, in spite of their location in continental interiors and often well-known geology, the subsidence driving mechanism and tectonic setting of these basins remains controversial. This volume presents both lithospheric and basin scale datasets acquired specifically to interrogate the tectonic process of cratonic basin formation. Focused on the Silurian to Triassic Parnaíba cratonic basin of Brazil, the papers discuss the results of a multidisciplinary basin analysis project comprising new geophysical, geological and geochemical data. This unique dataset enables the characterization of the lithospheric crust and mantle beneath the Parnaíba Basin, constrains the detailed evolution of the basin itself, and enables comparisons with cratonic basins globally. Several convergent themes emerge providing new and powerful constraints for models of the driving mechanisms of these enigmatic basins.
Keywords: Geology -- Brazil -- Parnaíba Basin Province.; Continental crust.; Cratons.; Basins (Geology); Lithosphere.; elektronické knihy; electronic books